A study on the evolving facet of anatomy education based on the learners’ perspective of medical students in Kolkata, India - Ray, Ansuman; Mandal, Lopamudra (Asian Journal of Medical Sciences, 2022)
Background: Anatomy education is dealing with tribulations and challenges, especially in the post-COVID period. Erosion of basic knowledge and time allocated to anatomy has caused great concern. As appraisal is an integral part of Medical Education, student evaluations can highlight divergent perspectives for the identification of existing lacunae and propose amendments. Aims and Objectives: This study was undertaken to reorganize the academic schedule and frame relevant recommendations for the enhancement of teaching standards in anatomy based on the learner’s perspective. Materials and Methods: A descriptive cross-sectional study was conducted among 876 MBBS students in Kolkata, India. A feedback response structured questionnaire was distributed to the students at the end of the 1st Professional MBBS for data collection. The template was generated in Microsoft Excel sheet and the results were analyzed to find out the possible solutions and actions required at regulatory levels including institutions, faculty, and medical students. Results: Anatomy was paradoxically perceived as the most interesting yet the most difficult curriculum. Complicated anatomical terms as well as rationed study specimens were significant impediments to understand anatomy. Dissection and demonstration with 10–20 students were optimal, while histology and lectures were considered redundant. The study underlined the need of reforms in the course module and academic schedule toward an integrated syllabus extended for 18 months. Conclusion: Conventional theoretical and experimental teaching should be blended with innovative inclusions based on scholar responses, in which the learner’s perspective is also emphasized, principally in the present online approach of education.